Effect of Surface Modification of Palygorskite on the Properties of Polypropylene/Polypropylene-g-Maleic Anhydride/Palygorskite Nanocomposites - David Cisneros-Rosado; Jorge Alonso Uribe-Calderon (International Journal of Polymer Science)
The effect of surface modification of palygorskite (Pal) on filler dispersion and on the mechanical and thermal properties of polypropylene (PP)/polypropylene grafted maleic anhydride (PP-g-MAH)/palygorskite (Pal) nanocomposites was evaluated. A natural Pal mineral was purified and individually surface modified with hexadecyl tributyl phosphonium bromide and (3-Aminopropyl)trimethoxysilane; the pristine and modified Pals were melt-compounded with PP to produce nanocomposites using PP-g-MAH as compatibilizer. The grafting of Pal surface was verified by FT-IR and the change in surface hydrophilicity was estimated by the contact angle of sessile drops of ethylene glycol on Pal tablets. The extent of Pal dispersion and the degree of improvement in both the mechanical and thermal properties were related to the surface treatment of Pal. Modified Pals were better dispersed during melt processing and improved Young’s modulus and strength; however, maximum deformation tended to decrease. The thermal stability of PP/PP-g-MAH/Pal nanocomposites was considerably improved with the content of modified Pals. The degree of crystallinity increased with Pal content, regardless of the surface modification. Surfactant modified Pal exhibited better results in comparison with silane Pal; it is possible that longer alkyl chains from surfactant molecules promoted interactions with polymer chains, thereby improving nanofiller dispersion and enhancing the properties.